Cupping Therapy as Thibbun Nabawi in Controlling Hypertension and Cholesterol - Abul A’la Al Maududi; Atila Sonmax; Krisna Aditya; Rika Purnama (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2026)
Hypertension is a major public health problem that increases the risk of cardiovascular diseases. Cupping therapy, as part of thibbun nabawi, is widely used as a complementary therapy in the management of hypertension. This study aimed to examine the effectiveness of cupping therapy in reducing blood pressure and cholesterol levels based on findings from previous studies. The method used was a literature review of national journals published between 2019 and 2024 employing pre-experimental and quasi-experimental study designs. The variables reviewed included systolic and diastolic blood pressure as well as total blood cholesterol levels. The results of the review indicate that cupping therapy has an effect on lowering blood pressure and cholesterol levels, although several studies reported methodological limitations. Cupping therapy has the potential to be used as a complementary therapy in hypertension management, while still emphasizing the importance of modern medical approaches.